2015
DOI: 10.1186/s12879-015-0806-2
|View full text |Cite
|
Sign up to set email alerts
|

Viral infections in outpatients with medically attended acute respiratory illness during the 2012–2013 influenza season

Abstract: BackgroundWhile it is known that acute respiratory illness (ARI) is caused by an array of viruses, less is known about co-detections and the resultant comparative symptoms and illness burden. This study examined the co-detections, the distribution of viruses, symptoms, and illness burden associated with ARI between December 2012 and March 2013.MethodsOutpatients with ARI were assayed for presence of 18 viruses using multiplex reverse transcriptase polymerase chain reaction (MRT-PCR) to simultaneously detect mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
19
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 12 publications
(15 reference statements)
9
19
1
Order By: Relevance
“…In this study, 57.7% were positive for at least one virus, which was similar to the morbidity rates reported in previous studies in Pittsburgh (59.7%) and Vitória of Southeast Brazil (54.3%) [15,25], but was different in China and compared with other reports [1, 3-5, 24, 26]. The single infection (89.8%) was predominant in our study, particularly the FluA virus (47.5%), which was consistent with previous reports in Shandong Province, Beijing, of China and other countries [5,[25][26][27][28][29]. sH3N2 and RhV coinfections were predominant among viral coinfections, which was different from previous reports [5,15,24,29,30].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, 57.7% were positive for at least one virus, which was similar to the morbidity rates reported in previous studies in Pittsburgh (59.7%) and Vitória of Southeast Brazil (54.3%) [15,25], but was different in China and compared with other reports [1, 3-5, 24, 26]. The single infection (89.8%) was predominant in our study, particularly the FluA virus (47.5%), which was consistent with previous reports in Shandong Province, Beijing, of China and other countries [5,[25][26][27][28][29]. sH3N2 and RhV coinfections were predominant among viral coinfections, which was different from previous reports [5,15,24,29,30].…”
Section: Discussionsupporting
confidence: 90%
“…In children with ARI, viral positivity rates range from 40 to 45% by IFA to 67-88% by molecular methods [6][7][8][9]. Viral positivity rates are lower in adults and can vary from 14 to 29% by IFA [10] to 66% by molecular methods [11].…”
mentioning
confidence: 99%
“…Previous research using the same methodology has shown that confirmed influenza compared with other respiratory viruses is more often associated with fever, 16 and is associated with a longer time to return to normal activities. 17 In adjusted multivariate regression analyses, the presence of unrevealed but PCR-confirmed influenza was the only significant correlate of influenza vaccination intention among currently unvaccinated children. Presence of confirmed influenza and lack of a high risk condition were significant correlates of influenza vaccination intention among unvaccinated adults.…”
Section: Discussionmentioning
confidence: 95%